Performance analysis of vertical axis wind turbine integrated with omni direction-guide-vane / Behzad Shahizare - Behzad, Shahizare (2017)
Wind energy is the conventional source of clean and renewable energy and it is the fastest-growing source of sustainable energy in the world. Numerical computation can offer important insight and data that are either difficult or expensive to measure or to perform tests experimentally. In this dissertation, we used the Computational Fluid Dynamics (CFD) to present effects of the Omni Direction Guide Vane shape on the performance of a H-rotor Vertical Axis Wind Turbine (VAWT). For this purpose, five straight-bladed VAWTs have been simulated via the Computational Fluid Dynamics (CFD). Hence, the VAWTs without the ODGV covering were simulated and validated via the Experimental Fluid Dynamics (EFD) data. The grid and time step independence test, as well as the effect of the domain size and turbulence model have been conducted. In the next step, the VAWT was shrouded by the ODGV cover and simulated by the coupling of the CFD and RSM method in different shapes and angle conditions. Results of this study indicates that the output power of the VAWT with α=55 º and β=20º ODGV guide vanes angles has been improved by 12%, 56% and 29% respectively at three different TSRs including 0.8, 1.2 and 1.6. Furthermore, all the shape ratios had a positive effect on the power and torque coefficient improvement when the TSR is higher than one. Moreover, results showed that the best case has a shape ratio of 0.55, which improves the power coefficient by 56%. In the final step, result of the optimized ODGV was compared with three different types of guide vanes in different flow angles. Results showed an optimized ODGV had the best improvement in terms of performance of the VAWT compared to the 4, 5, 6 bladed ODGVs. Optimized ODGV also showed the lowest sensitivity in different flow angles as well as being fabricated and tested in lab test conditions to validate the numerical findings.